1974
DOI: 10.2136/sssaj1974.03615995003800060030x
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Muleh Rate and Slope Steepness on Interrill Erosion

Abstract: Soil and water losses from plots representing field areas between rills were studied for four rates of straw mulch at four slope steepnesses. Three simulated rainstorms totaling 2 hours at 6.4 cm/hour were applied to a 61‐ by 61‐cm test area of Russell silt loam soil.Interrill erosion was reduced about 40% by mulch applied at a rate of only 0.5 metric tons/ha and about 80% by 2 tons/ha, as compared with no mulch. Erosion was negligible at the 8 tons/ha rate. Soil losses from the interrill areas at 20% slope we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
12

Year Published

1983
1983
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 0 publications
4
54
0
12
Order By: Relevance
“…The results obtained show that, annually, total plant cover is the main factor which explains runoff generation (Rs= -0.824) and the movement of sediments (Rs= -0.913). This concords with other studies (Grove & Rackham, 2001;Kosmas et al, 2000;Lattanzi & Meyer, 1974;Trimble, 1990) which found a (negative) linear relationship between the total volume of overland flow and the mass per unit of plant cover. In fact, plant cover decreases the kinetic energy of the rain that is released and dissipated to the soil surface, reducing the amount of detachment and, hence, the erosion that can occur (Greene & Hairsine, 2004).…”
Section: Relationship Between Variables (Statistical Analysis)supporting
confidence: 72%
“…The results obtained show that, annually, total plant cover is the main factor which explains runoff generation (Rs= -0.824) and the movement of sediments (Rs= -0.913). This concords with other studies (Grove & Rackham, 2001;Kosmas et al, 2000;Lattanzi & Meyer, 1974;Trimble, 1990) which found a (negative) linear relationship between the total volume of overland flow and the mass per unit of plant cover. In fact, plant cover decreases the kinetic energy of the rain that is released and dissipated to the soil surface, reducing the amount of detachment and, hence, the erosion that can occur (Greene & Hairsine, 2004).…”
Section: Relationship Between Variables (Statistical Analysis)supporting
confidence: 72%
“…Braida & Cassol (1996, 1999 observaram que, com o solo descoberto ou com doses de palha de trigo e de milho de até 0,2 kg m -2 , as taxas de perdas de água em entressulcos aumentavam inicialmente até um determinado tempo, a partir do qual tornavam-se estáveis, ao passo que doses de 0,4 e 0,8 kg m -2 de palha de trigo e de milho elevaram as taxas de perdas de água durante os 90 min de aplicação de chuva simulada de intensidade de 67 mm h -1 . Resultados semelhantes foram obtidos em laboratório por Lattanzi et al (1974).…”
Section: Resultsunclassified
“…La relación positiva pendiente-erodibilidad ha sido encontrada por autores que han trabajado en suelos desnudos, bien agrícolas, bien muestras trasporta-59 das al laboratorio (LATTANZI et al, 1974;SAVAT, 1978;POESEN, 1984;1986). Por el contrario otros autores han encontrado en suelos naturales que la mayor pendiente favorece la erosionabilidad de los suelos solamente hasta los 12 '.…”
Section: Discusión Y Conclusionesunclassified